Evaluation of platelet and its indices as a marker of neonatal sepsis: a prospective case control study - Choudhary, Ratana Ram; Makwana, Mohan; Mourya, Harish Kumar; Dabi, Jagdish; Gulati, Kartika (International Journal of Contemporary Pediatrics, 2018)
Background: Neonatal sepsis is major cause of neonatal morbidity and mortality worldwide. Blood culture and sepsis screening are currently used method, but their utility is limited due to delayed reporting and increased cost. Platelet indices are one such set of parameters which can be helpful in the future diagnosis of neonatal sepsis. This study was aimed to evaluate the significance of platelet indices either alone or in combination with existing sepsis screen as a marker of neonatal sepsis. Methods: Neonates admitted in the neonatal unit of Hospital and showing signs and symptoms of sepsis, and/or born to mothers with risk factor for sepsis were included in this study. Investigations sent for all these neonates included blood culture, sepsis screen (CRP, micro ESR, TLC, ANC, IT ratio) and platelet indices (Platelet count, MPV, PDW). Results: In present study, 81.12% neonates in case group had platelet count less than 1.5lacs/mm3 while in control group 20.91% neonates only had the same. This difference was statistically significant, (p<0.0001). Similarly, 70.91% neonates in case group had MPV more than >10.8 fl whereas in control group only 26.53% neonates had the same, with difference was statistically significant, (p<0.0001) Similarly, 65.81% neonates in case group and 34.69% in control group had PDW more than 19.1fl and this difference was statistically significant, (p=0.0001). Conclusions: High PDW, high MPV and low platelet count are more associated with neonatal sepsis. So, platelet and its indices may be used as a sensitive marker to identify septic babies and it may be combined with existing sepsis screen to specifically exclude non-septic case.